Formulation Of Dragon Fruit (Hylocereus polyrhizus) With Yellow Sweet Potato (Ipomoea batatas L.) Puree And Goroho Banana (Musa acuminafe, sp) Puree In Making Yoghurt - Rogi, Joshua T. A.; Mandey, Lucia C.; Taroreh, Mercy I. Riantiny; Tumbol, Michael; Kawengian, Shirley E. S. (Jurnal Agroekoteknologi Terapan, 2024)
In the era of functional food innovation, foods containing probiotics such as yogurt are known to offer significant health benefits to humans, not only in maintaining gut microbial balance but also in preventing various chronic degenerative diseases. This study aims to develop a functional beverage based on yogurt by incorporating red dragon fruit, yellow sweet potato, and goroho banana. This research employed a Completely Randomized Design (CRD) method with nine different treatments and three replications for each treatment. The parameters tested for their effects in this study were antioxidant activity, acidity level (pH value), and viscosity of the yogurt. The results of this study indicated that the best treatment for the formulation of dragon fruit yogurt, yellow sweet potato puree, and goroho banana puree was found in treatment A (Dragon Fruit Yogurt 100%) with antioxidant activity concentrations of 0.4 mg/g, 0.8 mg/g, 2.0 mg/g, 3.2 mg/g, 4.0 mg/g, and 4.8 mg/g, which were sequentially 22.76%, 40.97%, 61.31%, 76.48%, 86.34%, and 90.90% with an IC50 value of 0.67%. The acidity level (pH) was 3.28, and the viscosity was 4.75 cP. Keywords: yogurt, red dragon fruit, yellow sweet potato, goroho banana, antioxidant activity, probiotic